Diacylglycerols: healthy fats of the future? - Lai, Oi Ming (Universiti Putra Malaysia Press, 2017)
Malaysia is the fattest nation in South East Asia. A recent survey by Social Security Organization (SOCSO) Malaysia on 308,039 Malaysian employees in 2013 showed that 36.94% were overweight, 17.63% were obese, 13.14% had hypertension, 61.76% had hypercholesterolemia and 8.45% had diabetes (The Star, 27 Feb 2015). Malaysians’ present lifestyle and culture were among the reasons cited for the rise in these figures. Excessive intake of fat in the diet has been linked to diseases such as heart disease, cancer, obesity and possibly, gallbladder disease. Increased saturated fat intake is associated with high blood cholesterol and increased risk of coronary heart disease. It is difficult for individuals to change their dietary habits to reduce or minimize fat intake, while enjoying their favourite foods. This problem and the interest shown by consumers in structured lipids led to the search, by the food industry and scientific community, for “Healthy Fats of the Future”. Just as micronutrients have been lauded to prevent disease, so too has the effect of structured lipids like diacylglycerols (DAG) on obesity and weight-related disorders. The physiological effect of DAG is believed to be attributable to its metabolic pathway, which is different from the normal triacylglycerol metabolism. With structured lipids, we can combine the different positive and nutritionally valuable fatty acids in palm oil to produce a potent structured lipid with maximum benefits and minimum adverse effects. The main aim of this talk is to provide a comprehensive review of palm-based DAG with emphasis on the production, process developments, applications and animal trials.